2017
DOI: 10.1136/jmedgenet-2017-105073
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the relative effectiveness of the 2017 updated Manchester scoring system for predicting BRCA1/2 mutations in a Southeast Asian country

Abstract: Our results indicate that the updated MSS3 outperforms previous iterations and relative to the Manchester population, is just as effective in identifying patients with mutations in a Southeast Asian

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…Our small study showed the high accuracy of the Manchester scoring system for the prediction of pathogenic non-founder BRCA1/2 mutations in founder mutation-negative patients. Our finding is supported by several other studies performed on the validation of the Manchester scoring system in populations of UK, Germany and South East Asia [ 13 , 27 , 28 ]. However, larger numbers of cases are needed for comprehensive validation of these criteria in the population of Latvia.…”
Section: Discussionsupporting
confidence: 90%
“…Our small study showed the high accuracy of the Manchester scoring system for the prediction of pathogenic non-founder BRCA1/2 mutations in founder mutation-negative patients. Our finding is supported by several other studies performed on the validation of the Manchester scoring system in populations of UK, Germany and South East Asia [ 13 , 27 , 28 ]. However, larger numbers of cases are needed for comprehensive validation of these criteria in the population of Latvia.…”
Section: Discussionsupporting
confidence: 90%
“…The flow of article selection process is depicted in Figure 3 . After screening 544 records, 73 studies 10 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , …”
Section: Resultsmentioning
confidence: 99%
“…Several studies reported poor model performance in Asian breast cancer cohorts, including evaluation of Manchester Scoring System 14 and BOADICEA 10 in a Malaysian cohort of 187 patients with BRCA mutation rate of 14.4% 21 , and evaluation of BRCAPRO 11 and Myriad 12 in a Korean cohort of 236 patients with BRCA mutation rate of 19.5% 22 . In contrast, an updated Manchester Scoring System that included adjustment for breast cancer receptor status and high grade serous type ovarian cancer was shown to be equally effective in BRCA mutation prediction in the Singapore cohort as in the Manchester population 23 . In a cohort of 212 Chinese familial breast cancer patients with BRCA mutation rate of 15.6%, BRCAPRO, Penn II 16 , and Myriad models showed comparable accuracy to western cohorts 24 .…”
Section: Introductionmentioning
confidence: 88%